Risk Analysis of Computer Network Security Focusing on Phishing Attacks in Fintech Platform - Sangha, Zahra Kharisma; Sulistiani, Heni (LPPM STIKI Malang, 2024)
The advancement of Science and Technology, particularly in Information Technology such as the internet, has significantly facilitated individuals in achieving their life goals quickly, either through legal or illegal means. One prominent threat is phishing, which employs social engineering techniques to deceive users by impersonating authoritative entities. Phishing targets various industries, with the fintech platform sector being one of the primary targets. The main factors contributing to phishing in fintech platform services include users' lack of knowledge, psychological factors, and insufficient privacy protection on social networks. Therefore, computer network security is a critical measure to prevent phishing attacks on fintech platform services. This research employs a qualitative method with a descriptive approach.